Influência do exercício de natação sobre a regeneração do nervo mediano em ratos Wistar controles e obesos após protocolo de lesão por compressão nervosa - Coradini, Josinéia Gresele (2014)
Currently, obesity is considered a common nutritional disorder. It's one of the most relevant public health problems in modern society and a possible risk factor for carpal tunnel syndrome, the pathology that is most closely related to compression of the median nerve. This experimental study with a quantitative and qualitative approach aimed to evaluate the influence of the exercise of swimming on peripheral nerve regeneration in control and obese rates submitted to compressive lesion of the median nerve. Wistar neonates rats along their first 5 days of life received MSG subcutaneous injections (4g/Kg from their body weight at the day). The control group received hyperosmotic saline solution. 48 Wistar rats were used, divided into 6 groups: G1 (control), G2 (control with lesion), G3 (control with lesion + swimming), G4 (obese), G5 (obese with lesion) and G6 (obese with lesion + swimming). The nerve compression was induced through a surgical procedure. The treatment with swimming started on the 3rd day after surgery, and was applied 5 times per week with progressive durations. Before the lesion, the animals were submitted to nociceptive and strength assessments. These tests were repeated on the 3rd postoperative day and also during treatment on the 7th, 14th and 21st day. At the end of treatment, the animals were anesthetized and the median nerve was removed, processed for embedment in paraffin and prepared for protein analysis of BDNF and GAP-43. The data revealed that the pain threshold in the medial region, near the nerve compression, was lower in the second and third assessment when compared to the other assessments, and that groups G5 and G6 were the ones that showed lower nociceptive thresholds in the assessments. In the analysis of grip strength at the first evaluation, all groups are equal, but in the other reviews the G1 and G4 show themselves significantly different from the others. The G1 and G4 groups present organized structures, with myelin sheaths marked by osmium tetroxide. The other groups have a large tissue disorganization, with considerable loss of myelin sheath, however, it was possible verify recovery areas of the nerve fiber, by the the myelin sheath formation in groups G3 and G6. BDNF protein expression is higher in groups G3 and G6 when compared to G1 and G4 groups. The GAP-43 protein was only higher in G3 when compared to G1 and G4 groups. The exercise of swimming was able to enabling the axon regeneration process both in control rats and in obese ones, without difference between these groups, but It was not effective in improving the functionality of the affected limb as well as in the increase of the proteins studied